2012
DOI: 10.1016/j.aap.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with hit-and-run pedestrian fatalities and driver identification

Abstract: 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 Because hit-and-run crashes account for a significant share of pedestrian fatalities, a better understanding of these crashes will assist efforts to reduce pedestrian fatalities. Of the more than 48,000 pedestrian deaths that were recorded in the United States between 1998 and 2007 (Fatality Accident Reporting System [FARS]), 18.1% of them were the victims of hit-and-run crashes, and the percentage of fatal pedestrian hit-and-runs has been rising as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 12 publications
4
43
0
Order By: Relevance
“…Further, the analysis found younger children were more likely to be hit midblock during daylight and an increase during summer months but that road and weather conditions had no significant affect (DiMaggio and Durkin, 2002). Other studies suggest increased injury rates in males, less fatal injury in children, increased severity in mid-block crashes, and that about 18% of all pedestrian crashes are hit-and-run (Centers for Disease Control and Prevention Morbidity and Mortality Weekly Report, 2013; Stimpson et al, 2013;Slaughter et al, 2014;MacLeod et al, 2012;Rothman et al, 2012). However, as suggested by Ulfarsson et al, there is much variability in the literature making it unclear if these findings are generalizable to other geographic locations for use in targeted injury prevention initiatives (Ulfarsson et al, 2010).…”
Section: Current Pedestrian Crash Injury Knowledgementioning
confidence: 93%
“…Further, the analysis found younger children were more likely to be hit midblock during daylight and an increase during summer months but that road and weather conditions had no significant affect (DiMaggio and Durkin, 2002). Other studies suggest increased injury rates in males, less fatal injury in children, increased severity in mid-block crashes, and that about 18% of all pedestrian crashes are hit-and-run (Centers for Disease Control and Prevention Morbidity and Mortality Weekly Report, 2013; Stimpson et al, 2013;Slaughter et al, 2014;MacLeod et al, 2012;Rothman et al, 2012). However, as suggested by Ulfarsson et al, there is much variability in the literature making it unclear if these findings are generalizable to other geographic locations for use in targeted injury prevention initiatives (Ulfarsson et al, 2010).…”
Section: Current Pedestrian Crash Injury Knowledgementioning
confidence: 93%
“…However, despite the importance of the issue, we know very little about how these policies affect traffic safety or social and economic outcomes. Although studies have found that unlicensed drivers in general are more likely to be involved in accidents (20)(21)(22) and hit and run accidents (14,23,24), these studies do not examine the impact of policies that extend driver's license access to unauthorized immigrants. Unauthorized immigrants differ from other drivers without a valid license in that they face a risk of deportation and, therefore, might be more likely to leave the scene of an accident to avoid contact with the police.…”
Section: Significancementioning
confidence: 99%
“…2014found that in Ghana younger drivers (aged 25-44) and less experienced drivers were more likely to flee a collision, though others studies have suggested middle aged drivers (45-69) are more likely to flee (Tay et al, 2008;2010). Drivers are less likely to leave the scene if a victim is either very young or old (MacLeod et al, 2012) and drivers most likely to be identified when victims are young (MacLeod et al, 2012). Alcohol consumption is a common contributory factor in both collisions involving pedestrians (MacLeod et al, 2012) and damage-only cases (Jiang et al, 2016).…”
Section: Precursors To Collisions: Identifying Pre-collision Antecedentsmentioning
confidence: 99%